2008
DOI: 10.1016/j.fertnstert.2007.03.069
|View full text |Cite
|
Sign up to set email alerts
|

Differences in characteristics among 1,000 women with endometriosis based on extent of disease

Abstract: Objective-To determine the relationship between disease severity and patient characteristics in endometriosis.Design-Cross-sectional study of self-reported survey data. Setting-Academic research setting. Patient(s)-One thousand women in the Oxford Endometriosis Gene (OXEGENE) study. Intervention(s)-None.Main Outcome Measure(s)-Participants were assigned to one of two groups with predominantly revised AFS stage I-II (group I, n = 423) or III-IV disease (group II, n = 517). Their characteristics were compared by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
130
0
15

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(152 citation statements)
references
References 30 publications
7
130
0
15
Order By: Relevance
“…The prevalance of endometriosis in asymptomatic women in general population are not known, but pain is the most common symptom associated with endometriosis, diagnosed by visulization of pelvic organs via laparoscopy. Approximately three quarters of symptomatic patients experience nonmenstrual pelvic pain and/or dysmenorrhea (20). In the present study, all participants had different types of pain as follows: 91% had NCPP, 78% had dysmenorrhea, and 21.7% had dyspareunia.…”
Section: Discussionmentioning
confidence: 54%
“…The prevalance of endometriosis in asymptomatic women in general population are not known, but pain is the most common symptom associated with endometriosis, diagnosed by visulization of pelvic organs via laparoscopy. Approximately three quarters of symptomatic patients experience nonmenstrual pelvic pain and/or dysmenorrhea (20). In the present study, all participants had different types of pain as follows: 91% had NCPP, 78% had dysmenorrhea, and 21.7% had dyspareunia.…”
Section: Discussionmentioning
confidence: 54%
“…Moreover, one symptom that rarely appeared in the GP records was dyschezia, with only two cases and three controls being identified as suffering from this symptom. Since studies have shown that 29% of women with endometriosis experience bowel pain, 28 it would seem that dyschezia is either not being reported to GPs or is not being recorded in the GP medical records as dyschezia. This, together with the finding that abdominal pain was recorded frequently in women with endometriosis, may in part explain the reason for an increased diagnosis of IBS among women with endometriosis, with GPs possibly perceiving women's symptoms as bowel related.…”
Section: Discussionmentioning
confidence: 99%
“…28 These differences in fertility rates may arise from the broader age range in our population (15-55 years), with young women not yet experiencing fertility problems. It is also possible that there is an under-reporting of fertility problems in the GP records, although this is unlikely as GPs are required to record all major medical history and women in the UK generally access fertility services via the GP.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, it is also present in 20-40% of women undergoing IVF and is often associated with lower rates of live births, clinical pregnancy and implantation rates [3][4][5]. Women with Stage III and IV endometriosis can develop endometriomas, or cysts arising from ectopic endometrial tissue implanted in the ovary with invagination of the ovarian cortex.…”
Section: Introductionmentioning
confidence: 99%